Examining the fiduciary duties of the waqf trustee: Benchmarking with the law of trusts and Islam - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah; Ali, Zuraidah (Lexis-Nexis Malaysia Sdn. Bhd., 2018)
This article examines the fiduciary element in the role of waqf trustees and those delegated with powers over waqf management. It first examines waqf trustees and their duties. It then scrutinises the nature of fiduciary duties under the law, in particular and at more length, the fiduciary duty of trustees. In order to investigate whether waqf trustees have a fiduciary relationship with the donor and waqf beneficiaries, the article then examines the nature of fiduciary duties under the Shariah. The exposition applies fiduciary principles and practices governing trustees and endowment managers and compares this with Islamic principles of trust (Amanah) as a benchmark to assess the degree of duty owed by the waqf trustees. To ascertain whether the legal framework on waqf trustees in Malaysia contain any fiduciary elements, the law relating to waqf trustees in Malaysia is analysed with reference to relevant provisions in the waqf enactments and decided cases. It is found that the law on waqf contains some fiduciary elements but there is a general lack of awareness and minimum guidelines on the fiduciary nature of the duties of waqf trustees.